2018
DOI: 10.1111/nep.13189
|View full text |Cite
|
Sign up to set email alerts
|

5‐Aminolevulinic acid exerts renoprotective effect via Nrf2 activation in murine rhabdomyolysis‐induced acute kidney injury

Abstract: These findings indicate that ALA exerts its antioxidant activity via Nrf2-associated antioxidant factors to provide a renoprotective effect against rhabdomyolysis-induced AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…9,10 ALA reportedly exerts a broad range of cytoprotective effects against cisplatin-induced nephrotoxicity, rhabdomyolysis-induced acute kidney injury, hypoxia-induced cardiomyocyte injury, and low phosphorus loading-induced neurotoxicity through its antioxidant abilities. [10][11][12][13] Herein, we investigated the potential use of ALA as a novel radioprotective drug for normal rectal and bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 ALA reportedly exerts a broad range of cytoprotective effects against cisplatin-induced nephrotoxicity, rhabdomyolysis-induced acute kidney injury, hypoxia-induced cardiomyocyte injury, and low phosphorus loading-induced neurotoxicity through its antioxidant abilities. [10][11][12][13] Herein, we investigated the potential use of ALA as a novel radioprotective drug for normal rectal and bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Terada et al reported that cisplatin-induced nephrotoxicity and tubular apoptosis was prevented by ALA treatment; an effect that was mediated by five mitochondria-related proteins and enzymes: HMOX1, ATP5α, cytochrome c oxidase 4 (COX4), PGC-1α, and UCP2. 10 Other groups have indicated that ALA exerts antioxidant activity via nuclear factor erythroid 2-related factor 2 (Nrf2)-associated antioxidant factors to provide a renoprotective effect against rhabdomyolysis-induced injury, 11 ischemia-reperfusion injury, 30 and hypoxia-induced cardiomyocyte injury. 13 Although relevant proteins vary with the stresses and targeted organs, ALA administration exerts cytoprotective roles by maintaining mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…protect kidneys from acute injury [15,16]. Moreover, both in vivo and in vitro studies show that 5-ALA can induce heme oxygenase-1 (HO-1) expression in kidney cells [17,18].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…5‐ALA is an endogenous amino acid in animals and is the first compound produced by 5‐ALA synthase in the heme biosynthetic pathway . Recent studies have shown that 5‐ALA has cardioprotective, antifibrotic, antitumor, anti‐inflammatory, and antioxidative effects . Furthermore, 5‐ALA is known to induce HO‐1 expression in kidney cells, both in vivo and in vitro .…”
mentioning
confidence: 99%